1973
DOI: 10.1017/s0305004100048015
|View full text |Cite
|
Sign up to set email alerts
|

On Moore graphs

Abstract: In this paper, we shall first describe the theory of distance-regular graphs and then apply it to the classification of Moore graphs. The object of the paper is to prove that there are no Moore graphs (other than polygons) of diameter ≥ 3. An independent proof of this result has been given by Barmai and Ito(1). Taken with the result of (4), this shows that the only possible Moore graphs are the following:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 4 publications
0
85
0
1
Order By: Relevance
“…Unlike in the undirected case where nontrivial Moore graphs exist (the Petersen graph, the Hoffman-Singleton graph, and-possibly-graph(s) of degree 57 and diameter 2 of order 3250, cf. [12,1,10]), here it turns out that the equality n d;k ¼ M d;k holds only in the trivial cases when d ¼ 1 or k ¼ 1. The corresponding Moore digraphs are directed cycles of length k þ 1 and complete digraphs of order d þ 1.…”
Section: Introductionmentioning
confidence: 94%
“…Unlike in the undirected case where nontrivial Moore graphs exist (the Petersen graph, the Hoffman-Singleton graph, and-possibly-graph(s) of degree 57 and diameter 2 of order 3250, cf. [12,1,10]), here it turns out that the equality n d;k ¼ M d;k holds only in the trivial cases when d ¼ 1 or k ¼ 1. The corresponding Moore digraphs are directed cycles of length k þ 1 and complete digraphs of order d þ 1.…”
Section: Introductionmentioning
confidence: 94%
“…Second, two basic building blocks are interconnected by a link between two servers each in one building block without connecting any two switches directly. Although many efforts [13], [14] have been made to study the degree/diameter problem in graph theory, it is still open in the field of DCN.…”
Section: Motivation and Contributionsmentioning
confidence: 99%
“…However, Bannai and Ito [1] and Damerell [8] showed that a Moore graph with diameter D > 1 and valency k > 2 must have diameter D = 2 (and valency k ∈ {3, 7, 57}), hence the valency k of Γ should be 2. Therefore Γ is a heptagon, which finishes the proof.…”
Section: An Improved Bound For Diameter Threementioning
confidence: 99%